(untitled) (REMUNOM, 2026)
Polymorphism encompasses all discontinuities occurring within the same phase of the life cycle. The probable evolutionary sequence of polymorphism involved an initial differentiation, starting from the queen, along a size gradient, followed by the segregation of two distinct size groups and the elimination of intermediate sizes. Social bees have a female population divided into two castes (workers and queens) that are very different from each other, both morphologically and physiologically. Female ants are divided into three castes: workers, soldiers, and queens. Males, on the other hand, are not divided into castes, but in a more abstract sense, they can be considered a fourth caste. Differentiation patterns in social wasps are quite variable; there may be no dimorphism among females, with differences being only physiological and behavioral. Polymorphism is richest in Isoptera; juvenile stages are useful, their growth can be arrested or regressed, and both sexes are frequently socialized with function differentiation. The intra-specific polymorphism of social insect castes is responsible for a large part of the evolutionary success of this group.